Recurrent Bacterial Vaginosis: An Unmet Therapeutic Challenge. Experience With a Combination Pharmacotherapy Long-Term Suppressive Regimen. Issue 10 (October 2021) - Surapaneni, Sarvani; Akins, Robert; Sobel, Jack D.
Abstract : Background: Recurrence of bacterial vaginosis (RBV) is a major challenge to effective therapy. Women experiencing intractable and frequent recurrences are ill-served by available treatment options, such as both antimicrobial and use of probiotics. Methods: One hundred five women with RBV failing all recommended regimens seen in the clinic were prescribed combination oral nitroimidazole 500 mg twice a day for 7 days and simultaneous boric acid 600 mg daily per vagina therapy for 30 days; thereafter, they were prescribed twice-weekly vaginal metronidazole gel for 5 months in an attempt to prevent recurrence and followed by a 6-month observation period. Results reflect standard of clinic care in this uncontrolled retrospective cohort analysis. Results: An initial regimen of nitroimidazole and simultaneous but prolonged vaginal boric acid achieved a satisfactory response (BV cure ⩽2 Amsel criteria) in 92 of 93 available patients. Thereafter, a maintenance metronidazole gel prevented symptomatic BV recurrence in 69.6% of compliant patients at 6-month follow-up. Long-term cure at a 12-month follow-up was demonstrated in almost 69% of women reaching the 6-month observation phase. Vaginal candidiasis frequently complicated prolonged antibiotic prophylaxis requiring frequent antifungal rescue or prophylaxis. Frequent loss to follow-up in this long-term study influenced efficacy evaluation. Conclusions: In the absence of new antimicrobials or proven probiotic regimens, women with RBV may benefit from a prolonged drug-intensive antimicrobial regimen incorporating antibiofilm activity until newer measures are available. Additional randomized, control studies are needed. Abstract : Recurrence of bacterial vaginosis is common with few therapeutic solutions. A prolonged antimicrobial regimen incorporating antibiofilm activity produced encouraging results in 105 women with recurrent disease.